Energy and exergy analysis of an air source heat pump under variable ambient conditions - Streckienė, Giedrė; Kropas, Tomas; Mikučionienė, Rūta; Džiugaitė-Tumėnienė, Rasa (Journal of Environmental Engineering and Landscape Management, 2024)
Air source heat pumps (ASHPs) are becoming an increasingly popular heating source for buildings. The paper presents an evaluation of the experimental data from ASHP operation during the heating season in Lithuania when the problem of the evaporator’s surface freezing is visible. The performance of the air-to-water heat pump is examined using energy and exergy analyses performed by a coefficient of performance (COP), COPCarnot, exergy efficiency, and primary energy ratio. Analysis results show that the existing difference between the ideal and actual operation of ASHP represents the demand to improve the performance of ASHP evaporator. The actual COP was from 3.5 to 4.7 times lower than the Carnot COP. At 0 °C and 95% humidity, the ASHP’s performance was least favourable, with an average exergy efficiency of 0.21 and a COP of 1.49.